2019
DOI: 10.1039/c9cp00942f
|View full text |Cite
|
Sign up to set email alerts
|

Surface reconstruction causes structural variations in nanometric amorphous Al2O3

Abstract: Surface reconstruction is shown to exist in nanometric amorphous films of Al2O3, causing different short-range order at the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The coating appeared to be highly uniform in thickness, following the surface contour of the microcrystalline perovskite grains without any noticeable discontinuity (i.e., pinhole-free). The fast Fourier transform (FFT) pattern of the TEM image showed that the Al 2 O 3 layer was amorphous (Figure B, insets), consistent with the typical crystallinity reported in other ALD-coated Al 2 O 3 . The atomic ratio between Al and O, indicated in the energy-dispersive X-ray spectrum (EDS, Figure C), appeared to be close to the 2:3. This ratio matched with the expected stoichiometry of Al 2 O 3 , implying that the precursors were sufficiently reacted under the chosen conditions.…”
supporting
confidence: 80%
“…The coating appeared to be highly uniform in thickness, following the surface contour of the microcrystalline perovskite grains without any noticeable discontinuity (i.e., pinhole-free). The fast Fourier transform (FFT) pattern of the TEM image showed that the Al 2 O 3 layer was amorphous (Figure B, insets), consistent with the typical crystallinity reported in other ALD-coated Al 2 O 3 . The atomic ratio between Al and O, indicated in the energy-dispersive X-ray spectrum (EDS, Figure C), appeared to be close to the 2:3. This ratio matched with the expected stoichiometry of Al 2 O 3 , implying that the precursors were sufficiently reacted under the chosen conditions.…”
supporting
confidence: 80%